Analisis Keuntungan UMKM Teh Stevia Sweetson Di Desa Kolongan Atas II Kecamatan Sonder Kabupaten Minahasa - Horopu, Leodegario Alan; Manginsela, Elsje Pauline; Tarore, Melissa Lady Gisela (Sam Ratulangi University, 2023)
This study aims to analyze the profitability of Stevia sweetson tea MSMEs. This research was conducted from June to July 2023. Respondent selection was carried out using the survey method. The data used were primary data and secondary data. Primary data was collected through interviews with Stevia sweetson tea MSME business actors and the UNSRAT Student Creativity Program team. Secondary data were obtained from the Hukum Tua and the Sonder District Office, Minahasa Regency. Secondary data was also obtained from the internet through google scholar in the form of books, journal articles and theses related to the topic of this research, namely the profit analysis of Stevia sweetson tea MSMEs. The results showed that the profit obtained by Stevia swetetson tea MSMEs within three months on a land area of seventy square meters (70 m2) was IDR 3,786,339 with a total production of 15.1 kg of dried Stevia and fixed costs of IDR 34,343 total variable costs of IDR 2,219,318 and revenue of IDR 6,040,000. The calculation of the R / C ratio obtained is 2.7, this shows that every 1 rupiah spent is obtained 2.7 revenue. It is stated that it is greater than one (R / C> 1), which means that the Stevia sweetson tea MSMEs in Kolongan Atas II Village, Sonder District are economically profitable.*eprm*